IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF WORDWALL DALAM MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA DI MI - Endah Rohmatul Magfiroh; Imam Muslih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine how the use of wordwall interactive learning media can increase student’s interest and motivation in learning at Madrasah Ibtidaiyah (MI). This study uses a qualitative approach with a descriptive research type. The research subjects consisted of MI teachers and students who participated in the teaching and learning process using wordwall media. Data collection was carried out through direct observasition, interviews and document gathering. The data were analyzed through several steps, namely data reduction, data presentation and conclusion drawing. The results of the study indicate that the use of wordwall interactive media can create a more engaging, enjoyable and interactive learning atmosphere. The use of educational game features in wordwall makes students more involved in learning, increases their enthusiasm and encourages student participation during the learning process. In addition, this media also helps teachers to deliver material in a more varied and effective way. Students interest in learning is reflected in how actively they participate in leraning activities, while learning motivation is reflected in the increased enthusiasm of students when completing tasks and challenges given. Thus, the use of wordwall interactive media can be a good digital learning media option for increasing the interest and motivation of MI st udents to learn.